2003
DOI: 10.1002/jcp.10334
|View full text |Cite
|
Sign up to set email alerts
|

The non‐homologous end‐joining pathway is not involved in the radiosensitization of mammalian cells by heat shock

Abstract: A synergistic increase in cell killing is observed when a heat-shock is administered prior to, during, or immediately after exposure to ionizing radiation (IR). This phenomenon, known as heat-radiosensitization, is believed to be mediated by inhibition of repair of radiation-induced double strand breaks (DSB) when cells are exposed to temperatures above 42 degrees C. However, the mechanism by which heat inhibits DSB repair is unclear. The bulk of radiation-induced DSBs are repaired via the non-homologous end-j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
(70 reference statements)
1
11
1
Order By: Relevance
“…Our results do not prove that degradation of BRCA2 is the sole or even most important effect of heat on DNA repair or on other cellular processes relevant for cell killing. In fact, multiple hyperthermia targets have been described (29)(30)(31)(32)(33)(34). They do demonstrate, however, that hyperthermia can be a powerful, noninvasive tool to locally introduce BRCA2 degradation and HR deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Our results do not prove that degradation of BRCA2 is the sole or even most important effect of heat on DNA repair or on other cellular processes relevant for cell killing. In fact, multiple hyperthermia targets have been described (29)(30)(31)(32)(33)(34). They do demonstrate, however, that hyperthermia can be a powerful, noninvasive tool to locally introduce BRCA2 degradation and HR deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Since we have previously shown that Ku-dependent NHEJ is not involved in heat radiosensitization (39), by deduction one might assume that either D-NHEJ (alternative NHEJ) or HR, or both pathways, must also be implicated in heat radiosensitization, since Mre11 is known to function in both pathways. Using an siRNA approach, cells in which Mre11 was knocked down to 30–40% of control levels were significantly radiosensitized (42).…”
Section: Discussionmentioning
confidence: 99%
“…Such a finding (loss of activity of a critical repair enzyme after heat shock) would not be without precedent. Although Ku-dependent NHEJ is not involved in heat radiosensitization (39), the kinase and DNA-binding activity of DNA-PK and both Ku subunits, respectively, are known to decrease rapidly during hyperthermia treatment (45, 46). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ku80 becomes aggregated 54,55 and loses its activity rapidly after cells are heated 47,48,56,57 , but even before these findings (and indeed, the identification of the role of the Ku70/80 heterodimer in DSB repair), evidence for a role for Ku80 and for the NHEJ pathway itself in heat radiosensitization had been proposed 58 . However, Woudstra et al 59 and Dynlacht et al 55 have concluded that Ku and DNA ligase IV (and thus NHEJ) are not critical for heat radiosensitization and are suggestive that other pathways for DSB repair, notably HR, may be a target for radiosensitization. A review of pertinent studies concerning the role of NHEJ and HR in heat radiosensitization may be found elsewhere in this issue 60 .…”
Section: Introductionmentioning
confidence: 96%